Hepatic Encephalopathy Clinical Challenges and Opportunities - Ridola, Lorenzo; Riggio, Oliviero (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Hepatic encephalopathy (HE) is a complex neurological syndrome, characteristic of patients with liver disease, that causes a wide and complex spectrum of nonspecific neurological and psychiatric manifestations, ranging from a subclinical entity such as minimal or covert hepatic encephalopathy to a deep form in which a complete alteration of consciousness can be observed: overt hepatic encephalopathy. Both minimal and overt hepatic encephalopathy have a high impact on patients, caregivers, and national health services, driving substantial consumption of economic resources. In this Special Issue, we discussed the current state-of-the-art research, address ongoing knowledge gaps, and ongoing controversies related to the pathogenesis, diagnosis, and therapeutic management of hepatic encephalopathy.